A note on double conformable Laplace transform method and singular one dimensional conformable pseudohyperbolic equations - Eltayeb, Hassan; Mesloub, Said; Abdalla, Yahya T.; Kilicman, Adem (MDPI, 2019)
The purpose of this article is to obtain the exact and approximate numerical solutions of linear and nonlinear singular conformable pseudohyperbolic equations and conformable coupled pseudohyperbolic equations through the conformable double Laplace decomposition method. Further, the numerical examples were provided in order to demonstrate the efficiency, high accuracy, and the simplicity of present method.